Biochemical composition of follicular fluid in the three stages of follicular growth in alpacas - Tapia M., Gabriel (2020)
The aim of this study was to determine the concentration of glucose, total proteins, albumin, cholesterol and triglycerides in the follicular fluid during the three stages of follicular development in alpacas. Twenty-seven animals from CIP Chuquibambilla, National University of the Altiplano, Puno, Peru were used. The alpaca ovaries were checked by an Aloka SSD 500 ultrasound and a 7.5 MHz linear transducer. The animals were subjected to a follicular wave synchronization procedure in the presence of a follicle >7 mm. On day 9 of the synchronization the animals were distributed according to the stage of the follicular wave in three groups: G1, follicle >7 mm in the growing stage; G2, follicle >7 mm in the static stage; G3, follicle >7 mm in the regression stage. The follicular fluid was aspirated from the dominant follicle with the indicated ultrasound and a 5.0 MHz transvaginal transducer. The fluid was centrifuged, and the supernatant placed in vials and stored in liquid nitrogen. Biochemical determinations were made with specific commercial kits in a semi-automatic biochemical analyser. The results were: glucose 37.04, 41.19 and 30.07 mg/dl; total proteins 1.65, 1.93 and 1.79 g/dl; albumin 1.14, 1.42 and 1.31 g/dl; cholesterol 15.82, 18.3 and 11.08 mg/dl; triglycerides 11.3, 12.35 and 10.78 mg/dl for the stages of growth, static and regression, respectively, without significant differences between stages, with the exception of glucose. The glucose concentration was lower in the regression stage compared to the static stage (p<0.05).